(untitled) (Journal of Social Sciences Review, 2025)
This paper aims at to investigate Kushana`s era: the Rise of Gandhara civilization, the ancient regional political history which deems the Zenith of Gandhara civilization that met its climax in the Northwest of the Indian subcontinent. Gandhara as Greek had rich political history and tremendous contributions on the part of regional politico-historical discourse. In this paper it would be endeavored to address the Rise of Gandhara civilization by focusing on Kushana`s era. The employed design to address the question is historical and qualitative both in the term of collecting and analysis of the data. The consulted sources are archival documents, books, encyclopedias, reputed journals and historical literature associated to the present study. The Kushana`s era is the golden period of Gandhara civilization. Kanishka contributed enormously to the politico-historical development in the region. The role of religion in politics and shaping the international relation is the significant contributions in this context. Rise of Gandhara civilization reflect the splendid past being a great period of the region.